Emerging challenges, solutions, and best practices for digital enterprise transformation - Sandhu, Kamaljeet, 1970- (Advances in business strategy and competitive advantage., 2021)
"This book offers new developments in digital enterprise transformation of business systems from a global perspective, demonstrating the far-reaching impact for digital enterprise transformation, and suggesting ways that digital businesses are global and are continuously evolving online faster than ever and into new ecosystems in different parts of the world via internet. "--